Some Relevant Aspects of the Constituents of the English Tone Unit for Formal Pronunciation Teaching* Algunos aspectos importantes de los componentes de la unidad tónica inglesa para la enseñanza formal de la pronunciación - Nilton Hitotuzi (Profile: Issues in Teachers' Professional Development)
This paper is an attempt to provide evidence that the semantics of utterances can also be offered by intonation, and thus to point out some important aspects of the English intonation system for formal pronunciation teaching. Furthermore, on the assumption that this system plays a major role in aural/ oral communication, it argues for the necessity of long-term experiments on the applicability of David Brazil's Discourse Intonation approach with beginners. It nonetheless recognises that applying it to students in a foreign-language learning environment may pose a serious challenge for teachers whose mother tongue differs from the target language. Este artículo pretende evidenciar que la semántica de los enunciados también puede estar dada por la entonación, y de esa manera señalar algunos aspectos importantes del sistema de entonación del inglés para la enseñanza formal de la pronunciación. Además, partiendo del supuesto de que este sistema juega un papel importante en la comunicación oral, este artículo clama por la necesidad de experimentos a largo plazo sobre la aplicabilidad con principiantes del enfoque de entonación del discurso, de David Brazil. Sin embargo, se reconoce que la aplicación del mismo a estudiantes en un contexto de aprendizaje de lengua extranjera puede resultar un gran reto para profesores cuya lengua materna difiere de la lengua objeto.